Study on multidimensional shrinkage spatial-temporal patterns and driving forces of cities in the Yellow River Basin - Guangrui Xing; Dongfeng Wang; Wanxin Cai (Scientific Reports)
Abstract With economic globalization and the deepening process of industrialization and urbanization, China’s urban development has entered a vital transition stage. As one of the most influential rivers in China, the Yellow River Basin (YRB), with ecological protection and high-quality development as China’s national strategy, has not yet received sufficient attention for its urban shrinkage. Accordingly, this study constructs an evaluation index system for the shrinkage of cities in the YRB from four dimensions: population, economy, society and space. The entropy method and analytic hierarchy process are to determine the weights, the shrinkage model, the transfer matrix method and the exploratory spatial data analysis method are used to study the spatial-temporal evolution characteristics of 62 cities with data in the YRB. Random forest (RF) regression method was used to explore the influencing factors affecting the formation of urban shrinkage in the YRB and their influencing roles. The research results show that: (1) urban shrinkage in the YRB is characterized by spatial differentiation and shows a trend of drastic and concentrated development, with the shrinkage phenomenon becoming more and more significant; the degree of population shrinkage, economic shrinkage and social shrinkage is dominated by slight or moderate; the degree of space shrinkage and comprehensive shrinkage is dominated by high and heavy. (2) The reduction in the number of shrinking cities indicates a diminishing urban shrinkage across all dimensions, with a progressively increasing impact. (3) The accuracy of RF regression is high, and the main factors affecting the shrinkage of cities in the YRB account for 60.66%. An in-depth exploration of the characteristics of urban shrinkage and its development dynamics in the YRB from a multidimensional perspective will help to narrow the imbalance of urban development, promote high-quality development, and provide an essential reference to promote the progress of urban shrinkage research on a regional scale.